2009
DOI: 10.1371/journal.pone.0007044
|View full text |Cite
|
Sign up to set email alerts
|

Two Factor Reprogramming of Human Neural Stem Cells into Pluripotency

Abstract: BackgroundReprogramming human somatic cells to pluripotency represents a valuable resource for the development of in vitro based models for human disease and holds tremendous potential for deriving patient-specific pluripotent stem cells. Recently, mouse neural stem cells (NSCs) have been shown capable of reprogramming into a pluripotent state by forced expression of Oct3/4 and Klf4; however it has been unknown whether this same strategy could apply to human NSCs, which would result in more relevant pluripoten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…It is wellestablished that hESC, unlike murine ESC, do not require LIF either for maintenance of pluripotency or for differentiation along the neuronal lineage [34][35][36][37][38], although the LIF receptor components are expressed in both hESC [34] and primate ESC [37]. In contrast, LIF affects the in vitro maintenance and differentiation of NP cells isolated from fetal as well as adult human sources [17,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…It is wellestablished that hESC, unlike murine ESC, do not require LIF either for maintenance of pluripotency or for differentiation along the neuronal lineage [34][35][36][37][38], although the LIF receptor components are expressed in both hESC [34] and primate ESC [37]. In contrast, LIF affects the in vitro maintenance and differentiation of NP cells isolated from fetal as well as adult human sources [17,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Moreover, reprogramming by only two factors can be achieved, especially on less differentiated cells. [6][7][8][9][10] For mechanistic studies of reprogramming, mouse embryo fibroblasts (MEFs) are the most commonly used source of somatic cells. [10][11][12][13][14][15] These studies showed that reprogramming is largely a stochastic process that relies on multiple independent epigenetic events.…”
mentioning
confidence: 99%
“…This implicates different levels of changes in DNA factor binding, transcription and chromatin state [103] . Since the discovery by Takahashi (known as OKMS) could reprogram mouse embryonic and adult fibroblasts into induced pluripotent stem cells (iPSCs) [104] , the field of reprogramming has considerably evolved and several studies have reported the use of sets of these transcription factors in various combinations to reprogram mouse and human somatic cells [105][106][107][108] . More recently, murine B lymphocytes, liver, stomach and pancreatic b-cells were showed to reprogram into iPSCs using the combination of factors OKMS [109][110][111] .…”
Section: Epigenetic Changes During Nscs Reprogramming To Induced Plurmentioning
confidence: 99%